IDENTIFIKASI KESULITAN BELAJAR KIMIA PADA MATERI KONSEP MOL FASE E SMA SEMEN PADANG - Zakiah Wendi Afrilina; Dwi Finna Syolendra (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT The mole concept is frequently recognized as one of the most challenging topics in chemistry because it requires students to integrate abstract conceptual understanding, quantitative reasoning, and mathematical problem-solving simultaneously. These demands often lead to learning difficulties and misconceptions, which may subsequently hinder students' comprehension of stoichiometry and other advanced chemistry topics. This study aimed to identify the level of students' learning difficulties in the mole concept among Phase F students at SMA Semen Padang during the 2025/2026 academic year, as well as to explore the factors contributing to those difficulties. A mixed-methods approach with a descriptive design was employed by integrating quantitative and qualitative data. The study involved 29 students selected through random sampling. Data were collected using a two-tier multiple-choice diagnostic test, questionnaires, and interviews with both students and the chemistry teacher. Descriptive analysis was conducted by calculating the percentages of test and questionnaire results, which were subsequently integrated with interview findings to obtain a more comprehensive understanding. The findings revealed that 70.11% of the students demonstrated conceptual understanding, 28.05% exhibited misconceptions, and 1.84% did not understand the concept. The greatest learning difficulty was identified in the indicator related to gas volume under RTP/STP conditions, followed by mass calculation based on the mole concept. The major contributing factors included low learning motivation, limited study time, and insufficient mastery of prerequisite concepts. Integrating the diagnostic test, questionnaires, and interviews provided a more comprehensive profile of students' learning difficulties and contributed to a more holistic diagnostic assessment approach for supporting instructional planning and designing targeted remedial programs on the mole concept. ABSTRAK Materi konsep mol sering menjadi titik awal munculnya kesulitan belajar kimia karena menuntut peserta didik menghubungkan konsep abstrak, penalaran kuantitatif, dan prosedur perhitungan secara bersamaan. Kondisi tersebut berpotensi memunculkan miskonsepsi yang berdampak pada pemahaman materi stoikiometri dan topik kimia lanjutan. Penelitian ini bertujuan mengidentifikasi tingkat kesulitan belajar peserta didik pada materi konsep mol di kelas Fase F SMA Semen Padang Tahun Ajaran 2025/2026 sekaligus mendeskripsikan faktor-faktor yang memengaruhinya. Pendekatan mixed methods dengan desain deskriptif diterapkan melalui integrasi data kuantitatif dan kualitatif. Sampel penelitian dipilih menggunakan teknik random sampling, sedangkan pengumpulan data dilakukan melalui tes diagnostik two-tier multiple choice, angket, dan wawancara terhadap peserta didik serta guru kimia. Analisis data dilakukan secara deskriptif menggunakan persentase hasil tes dan angket yang kemudian dipadukan dengan temuan wawancara untuk memperoleh pemahaman yang lebih utuh. Temuan penelitian memperlihatkan bahwa 70,11% peserta didik telah memahami konsep, 28,05% masih mengalami miskonsepsi, dan 1,84% belum memahami konsep. Kesulitan terbesar muncul pada indikator volume gas pada kondisi RTP/STP, diikuti perhitungan massa berdasarkan mol. Faktor yang paling berkontribusi terhadap kesulitan belajar meliputi rendahnya motivasi belajar, keterbatasan waktu belajar, serta belum optimalnya penguasaan konsep prasyarat. Integrasi tes diagnostik, angket, dan wawancara memberikan gambaran yang lebih komprehensif mengenai profil kesulitan belajar sehingga dapat dimanfaatkan sebagai dasar penyusunan pembelajaran dan program remediasi yang lebih tepat sasaran.